A Bacterial Epigenetic Switch in Non-typeable Haemophilus influenzae Modifies Host Immune Response During Otitis Media - Robledo-Avila, Frank H.; Ruiz-Rosado, Juan de Dios; Partida-Sanchez, Santiago; Brockman, Kenneth L. (Frontiers in Cellular and Infection Microbiology, 2020)
Nontypeable Haemophilus influenzae (NTHi) causes multiple diseases of the human airway and is a predominant bacterial pathogen of acute otitis media and otitis media in which treatment fails. NTHi utilizes a system of phase variable epigenetic regulation, termed the phasevarion, to facilitate adaptation and survival within multiple sites of the human host. The NTHi phasevarion influences numerous disease-relevant phenotypes such as biofilm formation, antibiotic resistance and opsonization. We have previously identified an advantageous selection for a specific phasevarion status, which significantly affects severity and chronicity of experimental otitis media. In this study, we utilized pure cultures of NTHi variants in which modA was either locked ON or locked OFF, and thus modA was unable to phase vary. These locked variants were used to assess the progression of experimental otitis media and define the specific immune response induced by each subpopulation. Although the initial disease caused by each subpopulation was similar, the immune response elicited by each subpopulation was unique. The modA2 OFF variant induced significantly greater activation of macrophages both in vitro and within the middle ear during disease. In contrast, the modA2 ON variant induced a greater neutrophil extracellular trap response, which led to greater killing of the modA2 ON variant. These data suggest that not only does the NTHi phasevarion facilitate adaptation, but also allows the bacteria to alter immune responses during disease. Understanding these complex bacterial-host interactions and the regulation of bacterial factors responsible is critical to the development of better diagnostic, treatment and preventative strategies for these bacterial pathogens.